2002
DOI: 10.1111/j.1745-6606.2002.tb00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Reaching Insomniacs with Television PSAs: Poor Placement of Important Messages

Abstract: Most of the research conducted on the effectiveness of public service announcements has focused on improving internal characteristics of advertisements, such as message design and appropriate targeting. Scant research has been conducted on PSA effectiveness in terms of media placement. The purpose of this study is to estimate the audience coverage achieved by the broadcast television portion of the Ad Council's drunk driving prevention campaign. The results show that on average, only 11.2% of households in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Third, most of these studies have exhibited only small effects on behavior (Snyder & Hamilton, 2002). Finally, prior studies that have involved the use of televised PSAs for pregnancy prevention, HIV, and other sexually transmitted disease (STD) prevention have suffered from mistakes in campaign execution and lack of targeting (Flay & Sobel, 1983;Lancaster & Lancaster, 2002;Myhre & Flora, 2000).…”
Section: Mass Media Campaignsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, most of these studies have exhibited only small effects on behavior (Snyder & Hamilton, 2002). Finally, prior studies that have involved the use of televised PSAs for pregnancy prevention, HIV, and other sexually transmitted disease (STD) prevention have suffered from mistakes in campaign execution and lack of targeting (Flay & Sobel, 1983;Lancaster & Lancaster, 2002;Myhre & Flora, 2000).…”
Section: Mass Media Campaignsmentioning
confidence: 99%
“…Second, much of the research to date on such campaigns has involved radio (not television), and evaluations have not been rigorously controlled studies (see Myhre & Flora, 2000). Third, most of these studies have exhibited only small effects on behavior (Snyder & Hamilton, 2002 (Flay & Sobel, 1983;Lancaster & Lancaster, 2002;Myhre & Flora, 2000). …”
mentioning
confidence: 99%
“…Some broadcasters claim to run a large number of commercials in support of specific campaigns, but the spots tend to appear in late night or other fringe periods. Under even the best PSA schedules with the greatest number of spots, a review found the commercials reaching a small percentage of total households (Lancaster and Lancaster, 2002), and even this small audience might not have been the people desired for the campaigns. If no one sees the message, there exist serious doubts as to whether most of these campaigns possess hope of accomplishing anything, meaning that their only``value'' is to the people producing them.…”
mentioning
confidence: 99%
“…The literature reviewed in this chapter would seem to be most important for current and future work of PSAs and public communication campaigns in the specific areas of health and social issues (Kareklas et al, 2015;Mahoney, 2010;Lancaster & Lancaster, 2002;Lynn, 1974;Van Stee et al, 2012). For example, most of the earlier studies conducted were in specific areas of PSAs, such as HIV/AIDS prevention, anti-drugs, smoking and suicide prevention.…”
Section: Resultsmentioning
confidence: 99%
“…It is also agreed by Chan & Chang (2013) that PSAs are an important and persuasive way of disseminating information to people on public issues or government's programmes. Furthermore, PSAs have been consistently used around the world to inform and educate the public on social or health issues (Kareklas et al, 2015;Mahoney, 2010;Lancaster & Lancaster, 2002;Lynn, 1974;Van Stee et al, 2012) to help people improve their safety and welfare (Chan & Chang, 2013), and to reinforce community standards by discouraging improper behaviours that invoke public displeasure (Nabi, 2015 & Chang, 2013;Harakeh, Engels, Vohs, van Baaren, & Sargent, 2010;Kareklas et al, 2015;Mahoney, 2010 ;Van Stee et al, 2012).…”
Section: What Is a Public Service Announcements (Psa)?mentioning
confidence: 99%